Silverman-Anderson Score and Downes Score for Assessing Respiratory Distress in Newborns - Memon, Abdul Salam; Rafique, Muhammad; Lail , Amanullah; Khalid, Zainab; Abdul Sattar, Kulsoom; Danish , Malik Sohail (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To compare the effectiveness of the Silverman-Anderson and Downes scoring systems in predicting respiratory distress in newborns admitted to pediatric nursery. METHODOLOGY: A descriptive cross-sectional study was conducted in the neonatal nursery of Dr. Ruth K. M. Pfau Civil Hospital, Karachi, Pakistan, from July - December 2024, using non-probability consecutive sampling. The study included neonates within the first 24 hours of life of either gender and encompassed both term infants and preterm infants. Respiratory distress was defined by symptoms such as tachypnea, retractions, grunting, or cyanosis. The severity of respiratory distress was assessed using the Silverman-Anderson scoring system, which evaluated upper and lower thoracic depression, subxiphoid depression, nasal flaring, and expiratory grunting, and the Downes scoring system, which analyzed respiratory frequency, cyanosis, chest retractions, grunting, and lung sounds. Data were analyzed using SPSS version 24. RESULTS: Of 255 patients, the diagnostic accuracy of the Silverman-Anderson Scale in predicting respiratory distress showed a sensitivity of 91.04%, specificity of 63.3%, positive predictive value (PPV) of 46.92%, negative predictive value (NPV) of 95.2 % and an overall accuracy of 70.59%. The Downes Scoring demonstrated higher sensitivity (94.03%), specificity (68.09%), PPV (51.22%), NPV (96.97%), and overall accuracy (74.09%). The area under the curve (AUC) for Silverman-Anderson Scoring was 0.831 (95% CI 0.78–0.89), whereas Downes Scoring achieved a higher AUC of 0.885 (95% CI 0.84–0.93), indicating slightly better performance in diagnosing respiratory distress. CONCLUSION: While both systems demonstrated high diagnostic performance, the Downes score exhibited marginally superior diagnostic accuracy and predictive value.